2018
DOI: 10.1186/s10195-018-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Alleged malpractice in orthopaedics. Analysis of a series of medmal insurance claims

Abstract: BackgroundMedical malpractice is an important topic worldwide, and orthopedics is a clinical branch that is considered to be at a high risk for claims. The analysis of a series of medmal insurance claims allows forensic pathologists, clinicians, and insurance companies to probe the risk of a specific clinical branch for medical malpractice claims and highlights areas where care may be improved. We investigated the main features of a major Italian insurance broker’s archive in order to identify recurrent pitfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…Klemann et al have previously shown an increase in number of claims until 2012 and a stabilization after that in an investigation of all claims in the Netherlands from 2007 to 2016 [ 19 ]. A series of other studies could also not demonstrate an increase in the number of claims per year [ 4 , 9 ]. However, there are also a few European studies that did find an increase in claim incidence [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Klemann et al have previously shown an increase in number of claims until 2012 and a stabilization after that in an investigation of all claims in the Netherlands from 2007 to 2016 [ 19 ]. A series of other studies could also not demonstrate an increase in the number of claims per year [ 4 , 9 ]. However, there are also a few European studies that did find an increase in claim incidence [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 93%
“…As for the reasons of filing a claim, in this cohort the claim was often related to a delay in/wrong diagnosis or to (complications of) an elective operative procedure. Both in general and in orthopedic surgery, multiple authors have previously suggested diagnostic mistakes as the most common cause for a claim [ 9 , 23 ]. Injuries of the foot often have a large impact on functional recovery and, within the extremities, the highest number of missed fractures [ 24 , 25 ], which could also explain the high percentage of foot injuries in our cohort, especially in the subgroup analyses of diagnostic claims.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of clinical negligence claims comes from surgical specialties, orthopedic surgery being the worst offender, responsible for 29.8% of all cases [1]. Casali et al [6] carried out a retrospective study on orthopedic claims based on an archival data analysis from one of the largest medical malpractice insurance brokers in Italy. Their analysis indicates that orthopedics is the specialty with the highest risk of malpractice claims.…”
Section: Epidemiology Of Adverse Adventmentioning
confidence: 99%
“…In orthopedics, risk is mainly related to two types of procedures: diagnostic and therapeutic [6][7][8]. Therefore, subsequent discussion will be concentrated on these two types.…”
Section: Most Frequent Errorsmentioning
confidence: 99%
See 1 more Smart Citation